Penentuan Agama Pada Anak Dari Perkawinan Beda Agama (Studi Fenomenologi Penentuan Agama Pada Anak Dari Perkawinan Beda Agama) - Apriliyanti Apriliyanti (Journal of Comprehensive Science, 2026)
In society, interfaith marriage is an undeniable reality. Determining the religion of a child born from an interfaith marriage often becomes an issue within the household, particularly when both parents hold strong convictions regarding their respective faiths. This situation inevitably leaves the child confused about which religion to choose—the father's or the mother's? Ideally, a child should choose a religion they believe can truly serve as a guiding principle and anchor in their life. However, research conducted by the author indicates that the religion adopted by children of interfaith marriages is most often determined directly by their parents. From a cultural perspective, religion should be understood through the lens of ordinary people rather than solely through religious leaders. This study employs a qualitative descriptive research method. According to Sugiyono (2018:86), descriptive research is conducted to determine the value of independent variables—whether a single variable or multiple variables—without making comparisons or establishing relationships with other variables. Sugiyono (2018:9) defines the qualitative research method as an approach used to study objects in their natural setting, where the researcher acts as the key instrument; data collection utilizes triangulation (a combined approach), data analysis is inductive, and the findings emphasize meaning rather than generalization.